Effectiveness of a rectal cancer education video on patient expectations. (28th April 2022) - Streith, Lucas D.; Yip, Silas J. Y.; Brown, Carl J.; Karimuddin, Ahmer A.; Raval, Manoj J.; Phang, P. Terry; Ghuman, Amandeep
Abstract: Aim: Discrepancy between patient expectations and outcomes can negatively affect patient satisfaction and quality of life. We aimed to assess patient expectations of bowel, urinary, and sexual function after rectal cancer treatments, and whether a preoperative education video changed expectations. Methods: A total of 45 patients were assessed between January 2018 and January 2021 in a tertiary care hospital in Vancouver, Canada. Patients included were rectal cancer patients who had neoadjuvant chemoradiation and were listed for low anterior resection but had not yet had surgery. Following surgical consultation but before surgery, a questionnaire assessing expectations of lifestyle after treatments was administered. Patients then watched an educational video and repeated the questionnaire to assess for changes in expectations. Results: Patient scores indicated expectation that control of bowel movements, urination, and sexual function would sometimes be problematic, but had a range from occasionally problematic to good function. Significant change after the video was seen in the expectation of needing medications for bowel control, and 44%–69% of individual patient answers changed from prevideo to post‐video, depending on the question. The education video was scored as helpful or very helpful by 82% of patients. Conclusions: Patients have varying expectations of problematic control of bowel, urinary, and sexual function following rectal cancer treatments. A pretreatment education video resulted in a trend toward changed expectations for functional outcomes in most patients. Further educational modalities for patients may provide more uniform expectations of function and increase patient satisfaction after rectal cancer treatments.